2010
DOI: 10.3788/col20100804.0398
|View full text |Cite
|
Sign up to set email alerts
|

Dbr光纤激光器有效腔长测量新方法

Abstract: A novel method to measure the effective cavity length of distributed Bragg reflector (DBR) fiber laser with fiber Bragg grating (FBG) Fabry-Pérot cavity as the resonator is proposed. The effective cavity length of DBR fiber laser is accurately measured by measuring the frequency spacing of two adjacent longitudinal modes in the cavity without the precise physical length of FBGs. The measuring accuracy as high as 10 −5 mm can be obtained by setting the resolution bandwidth of the spectrum analyzer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Consequently, the difficulty in the acquisition of appropriate refractive materials results in the broadening of the PBG in the visible region. Second is the improvement of the model, including encapsulation, identification of defects [4,5] , nesting [6] , and multi-quantum well (MQW) [7−10] and its adoption which has become an effective method for broadening the band gap. Recent studies have shown that a multilayer dielectric reflector can have high reflectivity over a broad range of frequencies at all incident angles or an omnidirectional total reflection, if the refractive index and thickness of the constituent dielectric layers are chosen properly.…”
mentioning
confidence: 99%
“…Consequently, the difficulty in the acquisition of appropriate refractive materials results in the broadening of the PBG in the visible region. Second is the improvement of the model, including encapsulation, identification of defects [4,5] , nesting [6] , and multi-quantum well (MQW) [7−10] and its adoption which has become an effective method for broadening the band gap. Recent studies have shown that a multilayer dielectric reflector can have high reflectivity over a broad range of frequencies at all incident angles or an omnidirectional total reflection, if the refractive index and thickness of the constituent dielectric layers are chosen properly.…”
mentioning
confidence: 99%